THE STIGMA OF CANNABIS USE IN ACEHNESE CUISINE: CHALLENGES FOR HALAL TOURISM - Mulya Hafiz (Jurnal Analisa Sosiologi, 2025)
This study aims to analyze the impact of stigma on the use of cannabis in Acehnese cuisine and its implications for the sustainability of halal tourism. The method employed is qualitative with a literature review approach, analyzing secondary data from scientific journals, books, official documents, and media articles. The primary data sources include regulations on cannabis, its historical use in cuisine, and the negative and positive impacts of stigma. The findings reveal that social stigma toward cannabis, often associated with drug abuse, poses significant challenges for Acehnese cuisine. Although historically, cannabis was used as a cooking ingredient without psychoactive effects, shifts in public perception have affected the image of Aceh's halal tourism. As a result, this stigma has the potential to reduce Muslim tourists' interest in Acehnese cuisine and negatively impact the local economic sector.. This study provides a fresh perspective on the role of stigma in hindering the potential of Acehnese cuisine in the halal tourism industry. Its scholarly contribution enriches the literature on the relationship between social stigma, traditional culinary practices, and halal tourism, which has been rarely explored in depth. Methodologically, the literature-based approach focusing on regulatory, historical, and social perception analyses offers a model that can be applied to similar issues in other regions or cultural contexts.